Caveolin-1 Regulates Perivascular Aquaporin-4 Expression After Cerebral Ischemia - Filchenko, Irina; Blochet, Camille; Buscemi, Lara; Price, Melanie; Badaut, Jerome; Hirt, Lorenz (Frontiers in Cell and Developmental Biology, 2020)
Edema is a hallmark of many brain disorders including stroke. During vasogenic edema, blood-brain barrier (BBB) permeability increases, contributing to the entry of plasma proteins followed by water. Caveolae and Caveolin-1 (Cav-1) are involved in these BBB permeability changes. The expression of the aquaporin-4 (AQP4) water channel relates to brain swelling, however its regulation is poorly understood. Here we tested whether Cav-1 regulates AQP4 expression in the perivascular region after brain ischemia in mice. We showed that Cav-1 knock-out (KO) mice had enhanced hemispheric swelling and decreased perivascular AQP4 expression in perilesional and contralateral cortical regions compared to WT. GFAP-positive astrocytes displayed less branching and ramification in Cav-1 KO mice compared to WT animals. There was a positive correlation between the area of perivascular AQP4-immunolabelling and branch length of GFAP-positive astrocytes in WT mice, not seen in Cav-1 KO mice. In summary, we show for the first time that loss of Cav-1 results in decreased AQP4 expression and impaired perivascular AQP4 covering after cerebral ischemia associated with altered reactive astrocyte morphology and enhanced brain swelling. Therapeutic approaches targeting Cav-1 may provide new opportunities for improving stroke outcome.